Umpatan sebagai Penanda Relasi Keakraban Antar Mahasiswa: Analisis Berbasis Bentuk dan Gender - Salsabilla, Rika; Arimi, Sailal (MIMESIS, 2023)
Swear words using is considered low-value and inappropriate behavior in a normative society. There are differences between men and women in in the using of swear words. The purpose of this study was to identify the swearing lexicon along with the lingual forms and its references used by each gender. Also, to find out the frequency of its use and what factors trigger the use of swear words from each gender. Quantitative and qualitative approaches were used with data collection techniques through a questionnaire survey conducted on 115 students. The results of the study found that the choice of lexicon of swear words from the male gender is wider and more varied. Swearing is identified based on morphological and syntactic lingual forms. References of male gender come from groups of objects, animals, body parts, professions, situations, and activities. Meanwhile, references of female gender are more polite although they still seem rude, namely coming from groups of words such as animals, circumstances, activities, and objects. The frequency of use of both genders shows that the intensity of swear words using is rarely used.